Studies on the role of ion mass and energy in the defect production in irradiation experiments in tungsten. (2nd December 2021) - Maya, P.N.; Mukherjee, S.; Sharma, P.; Karki, V.; Singh, M.; Julie, S.; Kikani, P.; Satyaprasad, A.; David, C.; Pujari, P.K.; Deshpande, S.P.
Abstract: Experimental investigations on the role of ion mass and the primary knock-on atoms (PKA) spectrum in the defect type, structure and defect production efficiency is presented in ion-irradiation experiments in tungsten using a combination of positron annihilation spectroscopy, transmission electron microscopy and secondary ion mass spectroscopy. Recrystallized tungsten foils were irradiated using low- (helium), medium- (boron) and high-mass (gold) ions of MeV energy for a comparable dpa and implantation range at room temperature. Depending on the ion mass and the PKA spectrum, distinctly different defect structures were observed at the atomistic as well as meso-scales. While no indication of dislocation lines was observed in 3 MeV helium irradiated samples, the boron and gold ions showed extensive dislocation line formation. The cluster shape depends on the PKA energy and the cluster density depends on the irradiation fluence. The depth profile analysis of the defects in the helium-irradiated samples showed extensive helium trapping throughout the implantation range. Significant sub-surface helium trapping is observed within 700 nm from the surface, indicating that they moved towards the surface from their mean implantation depth of 4500 nm. The study also shows a correlation between carbon and helium profiles in the samples.